Optimizing The Performance Of Village Owned Enterprises - SUWITO, Suwito; JANNANG, Abdul Rahman (PT Keberlanjutan Strategis Indonesia, 2021)
This study aims to build a model for optimizing the performance of Village Owned Enterprises in the West Halmahera Regency. As a result of all that the existence of BUMDes has not been able to contribute to Village Original Revenue and improve the welfare of the village community as expected by the Village and the Community. To achieve this goal, the researcher used a qualitative approach with descriptive analysis methods. The results study found two findings that were effective for optimizing the performance of BUMDes. The first finding is that BUMDes must ensure market opportunities, availability of raw materials, product competitiveness, and product uniqueness to develop it is business. The second finding, using the AHP method, it is recommended that the Village of Guaemaadu develop the superior potential of the coastal tourism-based village industry; Hydroponic Farming; Coconut oil; Village Shop; Crafts from Bamboo; Coconut Collector; Hospitality; Processed Bananas; Nature Tourism and Village Bank.